Evaporative volatile organic compounds from gasoline in Mexico City: Characterization and atmospheric reactivity - V. Mugica-Alvarez; C. A. Martínez-Reyes; N. M. Santiago-Tello; I. Martínez-Rodríguez; M. Gutiérrez-Arzaluz; J. J. Figueroa-Lara (Energy Reports, 2020)
In 2016, only 4% of energy consumption in transportation came from renewables; then, use of fossil fuels will continue by several decades, with their corresponding evaporative and combustion emissions. Volatile organic compounds (VOCs) from gasoline evaporation were determined in Mexico City in order to know the emission of each compound to the atmosphere, as well as their ozone formation potential. Headspace technique was used to characterize the VOC evaporated mixture from different gasolines consumed in the city. Analyses of VOCs were carried out by chromatography with flame ionization detector. Composition of gasoline vapors was 18.40~±~4.43 for paraffin, 52.4~±~2.09 for iso-paraffin, 11.8~±~3.71 for olefins, 3.1~±~1.09 for naphthenes, and 12.1~±~3.23 for aromatics (% w/w), which is quite different of exhaust emissions from gasoline vehicles. The content of carcinogenic VOCs was 0.44~±~0.07 and 0.02~±~0.01 (% w/w) for benzene and 1,3-butadiene, respectively, but despite the small content, they should be reduced as much as possible to protect inhabitants health. Despite i-sopentane, methylpentanes, n-pentane, and the sum of trimethylpentanes, had the greater abundance in evaporative emissions, the major contributors to reactivity were the olefins contributing with 62% for the potential ozone formation, estimated with the maximum incremental reactivity.
Keywords: 330; Benzene; Evaporative emissions; Gasoline; Ozone; Reactivity; VOC